2003
DOI: 10.1080/j.1440-1614.2003.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Managers' Attitudes to the Physical Health of Their Patients

Abstract: Lack of coordination among health professionals and the health system may contribute to the poor general health of people with mental illness. Patients often have difficulty accessing general practitioners and the culture within the AMHS can exclude considerations of physical health. Case management should include aspects addressing the physical health issues of AMHS clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 12 publications
6
83
0
Order By: Relevance
“…These findings are supported by other work carried out in Melbourne and north London (Hyland et al 2003;Wright et al 2006). Hyland et al (2003) surveyed mental health case managers and found that physical health interventions were offered inconsistently and preventative health measures such as blood pressure were neglected.…”
Section: Addressing Motivation and Behaviour Changesupporting
confidence: 73%
See 1 more Smart Citation
“…These findings are supported by other work carried out in Melbourne and north London (Hyland et al 2003;Wright et al 2006). Hyland et al (2003) surveyed mental health case managers and found that physical health interventions were offered inconsistently and preventative health measures such as blood pressure were neglected.…”
Section: Addressing Motivation and Behaviour Changesupporting
confidence: 73%
“…Hyland et al (2003) surveyed mental health case managers and found that physical health interventions were offered inconsistently and preventative health measures such as blood pressure were neglected. The case managers believed that their core business was to assess and treat mental illness.…”
Section: Addressing Motivation and Behaviour Changementioning
confidence: 99%
“…The present study highlights the need for health professionals, including mental health professionals, to address barriers to adequately manage physical co-morbidity among those with mental disorders. Research among mental health professionals has identified barriers such as a lack of explicit allocation of responsibility for medical treatment, lack of service delivery integration, and pessimistic attitudes among treatment providers as to whether improved physical health is possible, or a priority, among those with mental illness (Brown et al 2000;Friedli & Dardis, 2002;Hyland et al 2003). Further research among primary-care providers and hospital physicians may be warranted to identify whether there are barriers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The latter findings contrast with the particular importance of referral and follow-up care in ensuring successful change in health risk behaviors. 48,53,54 The low levels of referral found in this study may be related to a number of possible barriers, including difficulties for clients in accessing a general practitioner or primary care physician [55][56][57] ; poor communication between mental health services, primary care, and other referral services 58,59 ; clinician perceptions that clients would not be responsive to behavior change [58][59][60][61] ; and a perceived lack of referral options. 58,[61][62][63] Despite such perceptions, evidence-based and readily accessible referral options (free government services) are available for clinician referral regarding smoking cessation (www.icanquit.com.au/further-resources/quitline) and inadequate nutrition and physical activity (www.…”
Section: Discussionmentioning
confidence: 84%